Degradación fotocatalítica de residuos industriales que contaminan afluentes de la región cundiboyacense por medio de pentóxido de vanadio y niobio. (2024)
Water is one of the most important resources that both the earth and humans possess, however, over the years, it has been contaminated by the effects of humans, their inventions, industry, revolution, waste and other factors that have affected it. In materials science, various methods and processes have been studied that allow improving water quality, degrading particles, separating various particles by different methods and processes, implementing different materials, which ultimately allow the development of improvement. The photocatalytic degradation of industrial waste by means of vanadium and niobium pentoxide is efficient in degrading polluting materials present in water such as rhodamine, methyl orange and eriochrome black, pollutants that are discharged in different sectors such as the industry: coal, textile, food, among others, because of this high levels of contamination have been reached, resulting in waters with a very low quality and not suitable for human consumption, however some sectors such as the agricultural sector, still use these waters for irrigation in different food crops, exposing users to different amounts of these pollutants, causing the development of diseases.